PENGARUH BEBERAPA RASIO KEUANGAN TERHADAP RETURN SAHAM PERUSAHAANKELOMPOK LQ45 DI BURSA EFEK INDONESIA PERIODE2010–2013 - Gamar Mana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2015)
The aimof this reserach is to analize influence of some financial ratio to the obligationreturn. To get data variable, it takes from financial report lq45 that list on indonesia Bursa Efek since2010-2013. With use analizing linier double. Methode this resutt show that variabel Total AssetsTurn Over (TATO), Return On Asset (ROA), Earing Per Share (EPS), and Price To Book Value(PBV) have it’s not significance to the obligation return with TATO (0.355), ROA (0.455), EPS(0.895), and PBV (0.678) up to (0.05). thevalue of determinasi (adjust R square) is as big 0.033,this result is the contribute as 0.033 or 0.033% from variable independent TATO, ROA, EPS, andPBV to the obligation return and while the rest is 96,7% explained by obligation return with othervariable. The value of small adjusted R Square means ability of independent variable in explainlimited independent variable. The nearest value of zero means independent that gives a bitinformation need to predict the dependent variable.